Fatony University, Pattani, Thailand - Hanik, Elya Umi; Susilowati, Retno; Islahuddin, Islahuddin (Pascasarjana IAIN Kudus, 2025)
This study aims to analyze and describe the implementation of differentiated learning at MI Darul Ulum 02 in Kudus and at MI Rodlotus Syubban in Pati within the framework of the Independent Curriculum. A qualitative field study with a multi-case design was conducted to collect data through interviews, documentation, and observation. The data were analyzed using multi-case analysis, beginning with an analysis of each case individually and then synthesizing the cases to identify patterns and distinctions. The findings reveal that differentiated learning at both madrasahs not only accommodates students’ diverse needs but also cultivates the Pancasila Student Profile through contextual learning. Differentiation is implemented through three dimensions—content, process, and product—supported by creating an inclusive and ethical learning environment, developing students’ personal and social competencies, and conducting diagnostic assessments for each subject. Practically, the study provides madrasah teachers with insight for designing and managing differentiated learning aligned with the Independent Curriculum. From a scientific perspective, this research contributes a contextual model of differentiated instruction in Islamic elementary schools by integrating national curriculum values with Islamic educational principles.